Learning with Light: Integrating Islamic Character Education into Multimedia Storytelling at Rural Elementary Schools - Faiz Azizi; Ach. Nurfuad Al-Fajri (International Journal of Instructional Technology, 2025)
This study aims to analyze the strengthening of Islamic character values through the implementation of digital storytelling in the learning process. The research is motivated by the need to present a contextual and engaging learning approach that aligns with the characteristics of the digital generation while maintaining Islamic moral principles. Employing a qualitative case study design, the research involved teachers and students in learning activities using digital media such as videos, audio recordings, and narrative slides featuring stories of the Prophets, companions, and Islamic moral tales. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that digital storytelling effectively instills Islamic character values such as honesty, responsibility, empathy, and care. Teachers act as innovators, transforming conventional lectures into interactive digital narratives, while students actively participate as creators of moral content, enhancing their moral understanding through direct experience. Moreover, the successful integration of digital storytelling is supported by the school’s religious culture and community involvement, including parents and local religious figures, who reinforce students’ moral environments. This study concludes that strengthening Islamic character education in the digital era requires not only the use of modern media but also the synergy of values, culture, and technology within a cohesive learning ecosystem.